Decolonising Bibles? Image, imagination, and imagin(in)g in the postcolonial academy - J. Punt (Acta Theologica)
The complicity of the Bible in the colonial endeavour is no longer seriously disputed. However, efforts to decolonise the Bible, biblical studies and their roles in colonising theology, that start with accounting for interpreters’ social locations, remain few and limited in scope. Ensconced in the image of ideologically secure and contented intellectual space, epistemological and hermeneutical approaches which explicitly involve the social location of interpreters and academic discourses are still viewed with concern if not suspicion. Antipathy towards cultural studies approaches such as postcolonial theory on the one hand is born from ideological preoccupation, intellectual comfort and turf-protection, but on the other hand deprives the biblical studies guild (and associated studies in theology and religion) from a broader spectrum of resources and reimagined engagements with biblical texts and their colonialist-infused legacies.